Los elementos esenciales del contrato de trabajo - Pacheco Zerga, Luz (Revista de Derecho, 2019)
The author examines the essential elements of the employment contract contained in the Labour Productivity and Competitiveness Law and its treatment by national jurisprudence and comparative law in order to identify the service relationships that correspond to the employment contract and grant social protection they deserve.